Advanced Proteomic Approaches to Elucidate Somatic Embryogenesis - Aguilar-Hernández, Victor; Loyola-Vargas, Víctor M. (Frontiers in Plant Science, 2018)
Somatic embryogenesis (SE) is a cell differentiation process by which a somatic cell changes its genetic program and develops into an embryonic cell. Investigating this process with various explant sources in vitro has allowed us to trace somatic embryo development from germination to plantlets and has led to the generation of new technologies, including genetic transformation, endangered species conservation, and synthetic seed production. Transcriptome data comparison from different stages of the developing somatic embryo has revealed a complex network controlling the somatic cell’s fate, suggesting that an interconnected network acts at the protein level. Here, we discuss the current progress on SE using proteomic-based data, focusing on changing patterns of proteins during the establishment of the somatic embryo. Despite the advanced proteomic approaches available so far, deciphering how the somatic embryo is induced is still in its infancy. The new proteomics techniques that lead to the quantification of proteins with different abundances during the induction of SE are opening this area of study for the first time. These quantitative differences can elucidate the different pathways involved in SE induction. We envisage that application of these proteomic technologies can be pivotal to identifying proteins critical to the process of SE, demonstrating the cellular localization, post-translational modifications, and turnover protein events required to switch from a somatic cell to a somatic embryo cell and providing new insights into the molecular mechanisms underlying SE. This work will help to develop biotechnological strategies for mass production of quality crop material.